Local Effects of Large New Apartment Buildings in Low-Income Areas - Asquith, Brian J.; Mast, Evan; Reed, Davin (The Review of Economics and Statistics, 2023)
We study the local effects of new market-rate housing in low-income areas using microdata on large apartment buildings, rents, and migration. New buildings decrease rents in nearby units by about 6% relative to units slightly farther away or near sites developed later, and they increase in-migration from low-income areas. We show that new buildings absorb many high-income households and increase the local housing stock substantially. If buildings improve nearby amenities, the effect is not large enough to increase rents. Amenity improvements could be limited because most buildings go into already-changing neighborhoods or buildings could create disamenities such as congestion.